Measuring R&D performance from an innovation systems perspective: an illustration from the Nigeria and Ghana agricultural research systems - Ragasa, Catherine; Abdullahi, Aliyu Sabi; Essegbey, George Owusu (International Food Policy Research Institute, 2011)
This paper combines elements of organizational design, institutional analysis, and innovation systems literature to empirically measure organizational performance of agricultural research agencies in Nigeria and Ghana. Results presented in this paper are limited to researchers' perceptions and measures at the national agricultural research organization (NARO) level, and are part of a larger ongoing research program that assesses the effectiveness of R&D investment in these countries.